Epidemiology and molecular phylogeny of Babesia sp. in Little Penguins Eudyptula minor in Australia. Issue 2 (August 2015) - Vanstreels, Ralph Eric Thijl; Woehler, Eric J.; Ruoppolo, Valeria; Vertigan, Peter; Carlile, Nicholas; Priddel, David; Finger, Annett; Dann, Peter; Herrin, Kimberly Vinette; Thompson, Paul; Ferreira Junior, Francisco C.; Braga, Érika M.; et al.
Highlights We examined blood smears from 263 wild little penguins in southeastern Australia. Babesia sp. was detected in penguins in New South Wales, Victoria and Tasmania. True prevalence is estimated between 3.4% and 4.5%. Babesia sp. from little penguins is closely related to B. poelea and B. uriae. Babesia infections were assymptomatic.